Genetic basis of the mucilage secretion ability associated with nitrogen fixation from aerial roots of maize inbred lines under low nitrogen conditions - Bowen Zhao; Xin Hou; Zhongliang Yu; Ronghui Zhang; Huixin Teng; Ziqiong Yang; Jianju He; Huijuan Wang; Zhihao Song; Jiankang Zheng; Bolin Song; Shiwei Ma; et al. (Crop Journal)
Recent studies have shown that mucilage secretion from aerial roots is an essential feature of modern maize inbred lines, with some retaining the nitrogen-fixing capabilities of ancient landraces. To explore the genetic basis of nitrogen fixation in mucilage and its evolution from teosinte (Zea mays ssp. mexicana) to modern maize, we developed a recombinant inbred line (RIL) population from teosinte and cultivated it under low-nitrogen conditions. Large-scale, multi-year, and multi-environment analyses of RIL-Teo, Doubled Haploid-A (DH-A), Doubled Haploid-B (DH-B), and association populations led to the identification of 15 quantitative trait loci (QTL), 68 quantitative trait nucleotides (QTN), and 59 candidate genes linked to mucilage secretion from aerial roots. Functional verification of the candidate gene ZmAco3, which is associated with mucilage secretion in aerial roots, demonstrated that deletion of this gene resulted in a reduction in mucilage secretion in aerial roots. In addition, most maize inbred lines exhibited stronger mucilage secretion from aerial roots under low-nitrogen conditions than under normal-nitrogen conditions. We categorized mucilage secretion into constitutive and low-nitrogen-inducible types. Through genotype-by-environment interaction studies, 8 QTL, 16 QTN, and 19 candidate genes were identified, revealing the genetic mechanisms underlying mucilage secretion under low-nitrogen conditions. These findings provide a comprehensive genetic analysis of the mucilage-secreting ability of maize aerial roots, contributing to our understanding of nitrogen fixation and offering potential avenues for enhancing nitrogen fixation in modern maize lines. This research advances knowledge of plant nutrient acquisition strategies and has implications for sustainable agricultural practices.